2017
DOI: 10.1007/978-3-319-57078-5_59
|View full text |Cite
|
Sign up to set email alerts
|

Toward Industry 4.0: Efficient and Sustainable Manufacturing Leveraging MAESTRI Total Efficiency Framework

Abstract: This paper presents an overview of the work under development within MAESTRI EU-funded collaborative project. The MAESTRI Total Efficiency Framework (MTEF) aims to advance the sustainability of manufacturing and process industries by providing a management system in the form of a flexible and scalable platform and methodology. The MTEF is based on four pillars: a) an effective management system targeted at process continuous improvement; b) Efficiency assessment tools to support improvements, optimisation stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Tools like MSM and ecoPROSYS complemented with an IS approach can enable the achievement of increased efficiency and valuable production while unlocking the inherent value of wasted resources. To support the development of self-organised IS, the MTEF includes [7]: a library of case studies and an exchanges database informing companies about possible uses for their waste streams and alternative input sources; a stepwise process to guide companies on the identification of their wasted resources, on valuing those resources and on building feasible IS-based synergies with other companies. This stepwise process, the T4IS presented here, provides a standardized and structured approach while maintaining a high degree of flexibility enabling its adaptation to different contexts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tools like MSM and ecoPROSYS complemented with an IS approach can enable the achievement of increased efficiency and valuable production while unlocking the inherent value of wasted resources. To support the development of self-organised IS, the MTEF includes [7]: a library of case studies and an exchanges database informing companies about possible uses for their waste streams and alternative input sources; a stepwise process to guide companies on the identification of their wasted resources, on valuing those resources and on building feasible IS-based synergies with other companies. This stepwise process, the T4IS presented here, provides a standardized and structured approach while maintaining a high degree of flexibility enabling its adaptation to different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…This responds to gaps identified during a practitioneroriented review of IS concept done by Holgado et al [3] that revealed the lack of supporting tools to identify, at early stages of ideation, the available opportunities for industrial symbiosis and to address the contextualization challenges of IS design and implementation. Specific support to self-organised IS included in the MTEF focuses on widening the knowledge on IS cases as a main source of information about uses of waste streams and alternative input sources, and on providing a structured, stepwise methodology for IS development, including waste identification, characterisation, valuing and exploitation [7]. This paper complements previous work [3] that reviewed the IS opportunities to assist practitioners in developing IS exchanges and networks.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Green Inbound and Outbound Logistics [33,41,42,44,59,[61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] Environmentally Consequently, increasing the ratio of value added to non-value-added activities through continuous improvement while minimizing (if not eliminating) harmful impacts of operational activities on the environment, natural resources, and all living things through waste elimination and responsible resource consumption have become the primary focus for gaining competitive advantages over other supply chains. In other words, it is essential for all corporations to develop a complete understanding of a truly sustainable operations and SCM activities.…”
Section: Current Trends In Supply Chain Management Referencesmentioning
confidence: 99%
“…Although theoretical and conceptual frameworks were quite detailed and definitive, no quantitative metrics were addressed across the two studies due to the nature of the proposed framework. In another recent study, Ferrera et al, (2017) provided an overview of MAESTRI total efficiency framework (MTEF) that combines continuous improvement, optimization strategies, and waste minimization theories with an Internet-of-Things infrastructure with a purpose of leveraging efficiency and sustainability of manufacturing industries [75]. The framework had emphasis on economic and environmental pillars of TBL, with an innovative perspective of Internet-of-Things (IOT) to alleviate current scalability issues.…”
Section: Past Lean-based Sustainability Assessment Frameworkmentioning
confidence: 99%